Wireless soft tactile sensor array system for interactive sensing - Lam, Jonnathan Shihao (Nanyang Technological University, 2020)
To show the potential of flexible sensors in the areas of interactive sensing, a wireless flexible tactile pressure sensor system was proposed. A soft tactile sensor array platform which include sensors, readout circuit and user application program was designed and implemented by the student. A PDMS-based resistive sensor was used. The readout circuit comprised of a Teensy microcontroller with a Bluetooth module. An Android-based user application program was developed. The user application program displays the pressure exerted as changes in color on the user interface. The resulting system was able to perform those functions, but with a 0.5- second lag.